The entrepreneurial experiences of black African women entrepreneurs in South Africa: The role of compensatory capital - Cross, Eunice (University of the Witwatersrand, Johannesburg, 2023)
This qualitative study explores the entrepreneurial experiences of black African women entrepreneurs in South Africa. These women have established growth orientated, scalable, and socially and economically impactful businesses. They operate in a diverse range of industries regarded as male-dominated and have harnessed financial resources for their businesses. The study illuminates the contextual structural constraints they encounter as business owners, and how they cultivate capital and position their agency towards sustaining their businesses and accessing finance around their structural constraints. More specifically, the study shows that black African women entrepreneurs from historically disadvantaged and marginalised backgrounds offer specific compensatory and learned resources that facilitate their integration, adaptation and inform their coping strategies in a challenging business environment. Data were obtained through semi-structured interviews with 28 participants in South Africa. The participants were identified using snowballing and purposive sampling. Data were inductively analysed using ATLAS.ti. Epistemologically, the study draws from Bourdieu’s theory of social practice and his concepts of field, habitus, and capital, and Cross and Atinde’s theory of compensatory capital, to map out the entrepreneurial experiences of black African women entrepreneurs. The findings relating to compensatory capital represent the main contribution of this study. Despite a progressive regulatory equality framework in South Africa, the research underscores that black African women entrepreneurs in South Africa are subjected to gender and racial discrimination, and patriarchal stereotyping in their business operation and fund- raising efforts. The findings revealed that the participants’ personal characteristics, motivations, skills, and knowledge, rooted in their earlier life experiences, assisted with navigating obstacles in their business environment. These include, amongst others, their confidence in their ability, dedication to hard work, resilience, optimism, and early-age entrepreneurial and financial skills, which influenced their later entrepreneurial behaviours. Further, the participants leveraged informational resources (academic qualifications, work experience, training, and networks) to enhance their competence, credibility, and competitive advantage in their business environment. Their social networks involved strategic alliances iii with men in the business environment who had legitimacy and capital highly valued to counteract gender and racial bias. The study lays a foundation for future empirical studies on the concept of compensatory capital in the field of entrepreneurship. The insights from this study and its recommendations may assist in the formulation of future policies and interventions in South Africa aimed at promoting women’s participation and advancement in entrepreneurship and enhancing their financial inclusion.
A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy (PhD), Johannesburg, 2023
Keywords: Black women entrepreneur; Women’s entrepreneurship; Marginalised; Compensatory capital; Bourdieu’s practice theory; UCTD; SDG-8: Decent work and economic growth